Grundtvig, Laub og kirkesangen - Thyssen, Peter (Grundtvig-studier, 1994)
Grundtvig, Laub and Church Singing.By Peter Thyssen The article deals with the importance that Grundtvig’s hymn writing acquired for the development of church music in Denmark through the 19. and 20. centuries. At first, the lack of tunes for the hymns written by Grundtvig for his own metres, resulted in the appearance of a great number of romantic hymn tunes which became widely used in church singing all over the country through the 19. century. Compared with these new lively and romantic tunes, however, the old chorales, isorhytmical at that time, were bound to seem more and more »stiff« and »dead« when used in the church service. Inspired by the reform movements in church music, which had developed in Germany since the 1840s, Thomas Laub (1852-1927), the organist and composer, advocated a restoration of the old chorale tunes in accordance with their original melodics, rhythmics, and tempo (in his book Om kirke-sangen (On Church Singing) from 1887). After his work on the restoration of the old church tunes in the years 1888-1910, Thomas Laub embarked in earnest on the task of composing new tunes for Grundtvig’s hymns (thus, out of 100 original hymn tunes by Laub, 68 were composed for hymns by Grundtvig). Laub’s hymn tunes were written with .the old church tone. as a source of inspiration, but are equally influenced by the late romantic tone of his own age.The point then is that Laub’s work on the historical and modem mode of expression of church music can be understood as a parallel to Grundtvig’s hymns, viz. as a »renewal on the foundation of the old church« - a programme that Laub himself explains in the book Musik og kirke (Music and Church) from 1920. Owing to this » Grundtvigian programme«, Laub’s tunes have not only achieved a unique congeniality with Grundtvig’s hymns; among Danish church composers Thomas Laub is also the one who has created the largest number of original hymn tunes still in use in church services in Denmark today. Thus, modem Danish church singing has been decisively influenced by the two »learned artists«, N.F.S. Grundtvig and Thomas Laub.